1995
DOI: 10.1038/373539a0
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of an integrin-binding fragment of vascular cell adhesion molecule-1 at 1.8 Å resolution

Abstract: The cell-surface glycoprotein vascular cell adhesion molecule-1 (VCAM-1; ref. 1) mediates intercellular adhesion by specific binding to the integrin very-late antigen-4 (VLA-4, alpha 4 beta 1; ref. 3). VCAM-1, with the intercellular adhesion molecules ICAM-1, ICAM-2, ICAM-3 and the mucosal vascular addressin MAd-CAM-1, forms an integrin-binding subgroup of the immunoglobulin superfamily. In addition to their clinical relevance in inflammation, these molecules act as cellular receptors for viral and parasitic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
138
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(141 citation statements)
references
References 27 publications
3
138
0
Order By: Relevance
“…By introducing interdomain disulfide bonds at the interface between fibronectin type III repeats 9 and 10, Altroff et al (43) have recently shown that maintaining a 28°angle of tilt between these domains results in higher-affinity interactions with integrin ␣ 5 ␤ 1 . The crystal structures of VCAM-1 domains 1 and 2 demonstrate that the relative orientation of the two domains is not fixed (40,41) and that there is a high degree of flexibility (ranging from 7.3-39.9°from five different crystal monomers) in the two-dimensional angle of tilt between the two domains (44). Perhaps removal of Ig-like domains COOH-terminal to domain 3 or merely substituting Asp 328 with Ala results in a subtle conformational change that maintains the angle between domains 1 and 2 such that the domain 1 C-D loop and domain 2 CЈ-E loop-E strand synergy site present an optimal integrin ␣ 4 ␤ 1 binding topology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By introducing interdomain disulfide bonds at the interface between fibronectin type III repeats 9 and 10, Altroff et al (43) have recently shown that maintaining a 28°angle of tilt between these domains results in higher-affinity interactions with integrin ␣ 5 ␤ 1 . The crystal structures of VCAM-1 domains 1 and 2 demonstrate that the relative orientation of the two domains is not fixed (40,41) and that there is a high degree of flexibility (ranging from 7.3-39.9°from five different crystal monomers) in the two-dimensional angle of tilt between the two domains (44). Perhaps removal of Ig-like domains COOH-terminal to domain 3 or merely substituting Asp 328 with Ala results in a subtle conformational change that maintains the angle between domains 1 and 2 such that the domain 1 C-D loop and domain 2 CЈ-E loop-E strand synergy site present an optimal integrin ␣ 4 ␤ 1 binding topology.…”
Section: Discussionmentioning
confidence: 99%
“…Also, removal of Ig-like domains COOH-terminal to domain 3 or simply substituting Asp 328 with Ala increases the relative affinity of 7D VCAM-1 for ␣ 4 ␤ 1 . Previous functional and structural studies of the two NH 2 -terminal domains of VCAM-1 (domains 1 and 2) have demonstrated that the primary ␣ 4 ␤ 1 binding site in domain 1 resides in a solvent-exposed loop (the C-D loop, which contains the essential residue Asp 40 ) (25,27,29,40,41). A secondary "synergy" site, the CЈ-E loop-E strand, is located in the upper face of domain 2 (30), spatially close to the C-D loop of domain 1 (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…These include VCAM, ICAM-1, ICAM-2, ICAM-3, and ICAM-5, and crystal structures are available for all (5)(6)(7)(8)(9)(10)(11)(12). All have two to nine IgSF domains, with N-terminal domains 1 and 2 (compared below) sufficient for integrin binding.…”
Section: Mucosal Addressin Cell Adhesion Molecule-1 (Madcam)mentioning
confidence: 99%
“…Structural studies on both rat and human CD2 (Jones et al, 1992;Bodian et al, 1994) have provided information on the adhesive interactions between IgSF domains; studies on VCAM-I (Jones et al, 1995) gave insight into IgSF/integrin adhesion. It is hoped that the structural analysis of this fragment of Sn will lead to information on the details of IgSF/carbohydrate interactions and their role in intercellular adhesion, and provide a template for studying other members of the recently characterized sialoadhesin family (Kelm et al, 1994a;Freeman et al, 1995).…”
mentioning
confidence: 99%